2004
DOI: 10.1177/09680519040100020301
|View full text |Cite
|
Sign up to set email alerts
|

Review: Molecular mechanisms of endotoxin tolerance

Abstract: The phenomenon of endotoxin tolerance has been widely investigated, but to date, the molecular mechanisms of endotoxin tolerance remain to be resolved clearly. The discovery of the Toll-like receptor (TLR) family as the major receptors for lipopolysaccharide (LPS) and other bacterial products has prompted a resurgence of interest in endotoxin tolerance mechanisms. Changes of cell surface molecules, signaling proteins, pro-inflammatory and anti-inflammatory cytokines and other mediators have been examined. Duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 130 publications
0
6
0
Order By: Relevance
“…Sensing of LPS is initiated by binding to circulatory LBP [55] and in this respect it is noteworthy to mention that expression of BPI/ LBP was more strongly down-regulated in L than in C. A complex of LBP and CD14 activates TLR4 [56], which is believed to play a pivotal role in LPS signaling in mammals. The marked differences in the LPS sensing between salmonid fishes and mammals can be due to the absence and/or functional differences of TLR4, which has not been identified to date [57] and accessory molecules including MD2, CD14, TRAM/TICAM2 and LBP.…”
Section: Discussionmentioning
confidence: 98%
“…Sensing of LPS is initiated by binding to circulatory LBP [55] and in this respect it is noteworthy to mention that expression of BPI/ LBP was more strongly down-regulated in L than in C. A complex of LBP and CD14 activates TLR4 [56], which is believed to play a pivotal role in LPS signaling in mammals. The marked differences in the LPS sensing between salmonid fishes and mammals can be due to the absence and/or functional differences of TLR4, which has not been identified to date [57] and accessory molecules including MD2, CD14, TRAM/TICAM2 and LBP.…”
Section: Discussionmentioning
confidence: 98%
“…The first type of innate memory described in mammals is known as "endotoxin tolerance" and results in a less potent secondary response to gram-negative endotoxin or other bacterial challenges, aiming at attaining sufficient protection while avoiding the substantial damage to the host tissues and organs that can be caused by a full innate/inflammatory response, which includes the deadly endotoxin shock (8)(9)(10)(11). In other cases, e.g., in the case of exposure to the tuberculosis vaccine BCG or to the fungal b-glucan, the memory response results in a potentiated reaction ("trained immunity") (6,12).…”
Section: Introductionmentioning
confidence: 99%
“…This would contribute on one side to the implementation of a more thorough safety evaluation of AuNPs and, on the other hand, it could open the way to a targeted use of this nanomaterial for the therapeutic modulation of innate immunity/inflammation in several immune-related and inflammatory diseases. In particular, this study has addressed innate memory, i.e., the ability of monocytes/macrophages to activate a more protective reaction to a challenge when previously exposed to the same or a different infectious agent(6,7,(9)(10)(11)(12)(13)(14)(15)(16)(17). Following previous studies showing that endotoxin-free Au and other NPs are essentially unable to induce innate/inflammatory responses and innate memory per se, but could at least in part modulate the memory induced by microbial agents(21)(22)(23)(24)(25)(26)72), here we have examined if the nature of the memory-inducing microbial agents could determine the capacity of AuNPs to interfere with the development of innate memory.…”
mentioning
confidence: 99%
“…5 It is well known that innate immune cells during various types of infection undergo protective adaptations and one of such adaptive mechanisms is ET, in which cells enter into a transient unresponsive state and are unable to respond to further challenges with endotoxin. [7][8][9] Since GCs behave like immune cells and, therefore, we hypothesized that GCs can also undergo tolerance. Accordingly, we have mimicked the ET by repeated exposure of endotoxin to GCs till the GCs become unable to respond endotoxin in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…6 One such adaptive mechanisms is endotoxin tolerance (ET), in which cells enter into a temporary insensitive state and are unable to respond to further challenges with endotoxin. [7][8][9] Many studies in immune cells have shown that the repeated exposure with endotoxin leads to the reduced ability of cells to secrete proinflammatory cytokines. 10 Similarly, we hypothesized that the TLRexpressing GCs can induce immunity as well as undergo tolerance.…”
mentioning
confidence: 99%